Physical vulnerability of masonry building to the slow-moving landslide: insight from numerical simulation - Wang, Haojie; Mao, Jiarui (Frontiers in Earth Science, 2025)
Slow-moving landslides, characterized by sustained destructive potential, are widely distributed in northwest China. However, research on the damage mechanisms of masonry buildings caused by slow-moving landslide-induced surface deformation is significantly lacking, which severely restricts the physical vulnerability assessment of masonry structures and the quantitative risk evaluation of slow-moving landslides. Through field investigations, CDEM numerical simulations, and statistical analyses, this study reveals the cooperative deformation characteristics and progressive failure mechanisms of masonry buildings subjected to ground cracks in slow-moving landslides, and establishes physical vulnerability curves for four distinct ground crack scenarios. The key findings indicate that masonry buildings affected by slow-moving landslides primarily exhibit transverse wall cracking and longitudinal wall inclination due to ground crack propagation. As crack propagation continues, the first-floor walls exhibit significantly higher Mises stresses compared to those on the second floor. Wall inclination rates demonstrate a distinct threshold effect during crack propagation: below the threshold, inclination increases linearly with crack displacement, while above the threshold, it exhibits exponential growth. Under identical crack displacement conditions, wall inclination rates decrease in the following order: horizontal tension, combined tension, settlement, and combined uplift scenarios. The differential effects of these scenarios on wall inclination become more pronounced with increasing crack displacement. Weibull functions were employed to fit vulnerability curves for masonry structures under four ground crack scenarios, revealing displacement thresholds of 22 cm, 26 cm, 27 cm, and 37 cm for complete structural vulnerability (V = 1) in each respective scenario. These findings provide valuable insights for vulnerability prediction and emergency rapid assessment of buildings subjected to slow-moving landslides across various disaster scenarios.